Evaluation of FDG PET combined with cardiac MRI for the diagnosis and therapeutic monitoring of cardiac sarcoidosis. Issue 1 (January 2019) - Sgard, B.; Brillet, P.-Y.; Bouvry, D.; Djelbani, S.; Nunes, H.; Meune, C.; Valeyre, D.; Soussan, M.
Abstract : AIM: To compare combined 2-[ 18 F]-fluoro-2-deoxy-d- glucose (FDG)-positron-emission tomography (PET) and cardiac magnetic resonance imaging (CMR) for the diagnosis and therapy monitoring of cardiac sarcoidosis (CS). MATERIALS AND METHODS: Eighty patients with sarcoidosis and a suspicion of CS who underwent PET and CMR were included retrospectively. PET was undertaken after a low-carbohydrate–high-fat diet in all patients using a combined 16-section PET/computed tomography (CT) camera. PET was considered positive (PET+) in cases of focal or multifocal FDG uptake. CMR was considered positive (CMR+) in cases of subepicardial late gadolinium enhancement (LGE). A subgroup of 50 patients (50/80) was monitored during therapy and classified as responders or non-responders. RESULTS: Eighty-two percent of patients with PET+ (9/11) also had CMR+ imaging, with good spatial agreement (kappa=0, 79; 95% confidence interval [CI]: 0.65–0.94). Twenty-seven percent (22/80) had residual physiological FDG uptake, with a standardised uptake value (SUV) not significantly different compared to the SUV from pathological uptake (6.4 versus 6 respectively, p =0, 92). The clinical response was more frequent in patients with baseline PET+ compared to baseline PET– (80% versus 45%, p =0.07). PET findings improved in all cases under treatment (7/7), whereas LGE improved in only 33% of patients (3/9). CONCLUSION: Due to high risk of false-positive or undetermined findings, PET might be performed as a second-line study in cases of LGE, to assess inflammatory load. In addition, PET seems suitable to predict and assess response under therapy. Highlights: Semi-Quantitative analysis of FDG uptake is not a reliable criterion for the diagnosis of inflammatory cardiac sarcoidosis. FDG uptake during cardiac sarcoidosis has a good spatial agreement with LGE-CMR. The high risk of false positive results suggests that PET should be performed as a second-line test in case of LGE-CMR. FDG PET is more sensitive than CMR for predicting therapeutic response in patients with CS.